Penyuluhan Pemanfaatan Energi Terbarukan (PLTS) di SMP IT Almaka Jakarta - Christiono Christiono; Samsurizal Samsurizal; septianissa azzahra; Rizki Pratama; Titi Ratnasari; Miftahul Fikri (Terang, 2019)
The use of solar energy as an alternative to fossil fuels for electricity generation is increasingly being carried out nowadays. considering the decreasing oil reserves and also the environmental pollution that they cause. in order to increase the utilization of solar energy utilization in Indonesia, it is necessary to conduct socialization or introduction to various elements of society, especially students, so that it is expected to provide understanding and will also increase the utilization of solar cells in the future. socialization of Renewable Energy Utilization (PLTS) carried out at SMP IT ALMAKA Jakarta was conducted by giving an introduction to how solar cells work, problems regarding solar cells and how to apply solar cells to meet the electricity needs of the community. The presentation was conducted with an interactive method with theoretical exposure, demonstration of how to use solar cells, and question and answer sessions. the results obtained were that the participants seemed enthusiastic and able to understand how to apply solar cells seen in the question and answer session. so that participants who are the younger generation are expected to be able to develop and utilize the use of solar cells for future energy sources